2014
DOI: 10.1111/opn.12061
|View full text |Cite
|
Sign up to set email alerts
|

Discovering intergenerativity: an evaluation of learning partnerships between student nurses and older adults

Abstract: Involving older adults as education partners in undergraduate nursing programmes has benefits for all participants and could form a valuable component of any undergraduate nursing programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Relatively fewer studies have assessed older adults’ perceptions, attitudes, and health changes after HP student clinical or educational interventions. Programs described in the literature involve students in nursing ( du Plessis et al, 2013 ; Latimer & Mezey, 2001 ; Livsey et al, 2020 ; Reitmaier et al, 2015 ), physical therapy ( Vincenzo & Patton, 2021 ), dentistry ( Hjertstedt et al, 2014 ; Northridge et al, 2017 ), and medicine ( Liang En et al, 2011 ). Additional studies represent collaborative efforts between students of different disciplines: Medical and nurse practitioner students ( Kaplan et al, 2017 ; Kata et al, 2018 ); exercise physiology, physical therapy, nursing, and nutrition students ( Seymour & Cannon, 2010 ); and nursing, nutrition, and pharmacy students ( Lee et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively fewer studies have assessed older adults’ perceptions, attitudes, and health changes after HP student clinical or educational interventions. Programs described in the literature involve students in nursing ( du Plessis et al, 2013 ; Latimer & Mezey, 2001 ; Livsey et al, 2020 ; Reitmaier et al, 2015 ), physical therapy ( Vincenzo & Patton, 2021 ), dentistry ( Hjertstedt et al, 2014 ; Northridge et al, 2017 ), and medicine ( Liang En et al, 2011 ). Additional studies represent collaborative efforts between students of different disciplines: Medical and nurse practitioner students ( Kaplan et al, 2017 ; Kata et al, 2018 ); exercise physiology, physical therapy, nursing, and nutrition students ( Seymour & Cannon, 2010 ); and nursing, nutrition, and pharmacy students ( Lee et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing numbers of elders and age-associated comorbidities, especially dementia, have become a challenge for nursing students because they have to learn how to communicate with these patients effectively [7][8][9][10][11]. Therefore, the development of relational skills during clinical training in institutions that care for elders is essential for preparing this new generation of professionals.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to change the attitudes of these nursing students towards caring for cognitively impaired elders to ensure that they will have improved practices as future nurses. This development will boost a differentiated care strategy capable of responding to complex chronic health needs associated with aging [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new intergenerational learning paradigm can address this, by emphasizing the importance of intergroup contact between generations, where each group can learn from and teach the other through reciprocal relations between different generations (Kuehne and Melville, 2014). The experience of an undergraduate nursing programme (Reitmaier et al, 2015), demonstrated the benefits of intergenerational contact between older and younger adults, one of which is the development of intergenerativity. Intergenerativity (George et al, 2011) describes a process from which different generations develop an ability to create, generate or produce new content together.…”
Section: Introduction and Theoretical Contextmentioning
confidence: 99%